2019
DOI: 10.1039/c8cp06908e
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the intrinsic reactivity of molecules through non-covalent interactions

Abstract: Non-covalent interactions as tools for modifying molecular properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Cooperativity has been considered as the characteristic feature of secondary interactions in the literature. [6,[8][9][10][60][61][62][63][64][65][66][67] That is, the intermolecular distance decreases as the intermolecular binding energy increases when the number of molecules involved in the complex increases.…”
Section: Cooperativity Induced By Polarizationmentioning
confidence: 99%
“…Cooperativity has been considered as the characteristic feature of secondary interactions in the literature. [6,[8][9][10][60][61][62][63][64][65][66][67] That is, the intermolecular distance decreases as the intermolecular binding energy increases when the number of molecules involved in the complex increases.…”
Section: Cooperativity Induced By Polarizationmentioning
confidence: 99%
“…In each of the chalcogen, pnicogen, tetrel, and triel bonds, an atom of that same particular family of the periodic table replaces the bridging proton of the H-bond. Among these interactions, the halogen bond (XB) is arguably the one that has been acknowledged for the longest time and has engendered the greatest amount of scrutiny. Extensive study has demonstrated that the XB owes its stability to several factors. In the first place, the electron-density cloud surrounding the X atom is quite anisotropic; while the overall charge on the X atom is partially negative, there is a pocket of positive potential that lies along the extension of the covalent C–X bond, which is commonly referred to as a σ-hole. This positive region attracts the negative potential of an approaching nucleophile, for example, its lone pair, leading to a Coulombic attraction.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The formation of alkaline-earth bonds results in a significant electron density redistribution of the Lewis base interacting with the Be or Mg derivative, modifying the Lewis base reactivity. 13,14 The consequence is that the formation of alkaline-earth bonds modulates the strength of other non-covalent interactions in which the Lewis base participates, such as hydrogen bonds, 15,16 halogen bonds, [17][18][19] or tetrel bonds. 20,21 They also contribute to create σ-holes, 22 or to spontaneously produce radicals.…”
Section: Introductionmentioning
confidence: 99%